Genome-wide association study for milk yield, frame, and udder-conformation traits of Gir dairy cattle - Dominguez-Castaño, P. [UNESP]; Fortes, M.; Tan, W. L.A.; Toro-Ospina, A. M.; Silva, J. A. II V. [UNESP] (American Dairy Science Association, 2024)
Genome-wide association studies are employed to identify genomic regions and candidate genes associated with several traits. The aim of this study was to perform a GWAS to identify causative variants and genes associated with milk yield, frame, and udder-conformation traits in Gir dairy cattle. Body conformation traits were classified as “frame,” and “udder” traits for this study. After genotyping imputation and quality control 42,105 polymorphisms were available for analyses and 24,489 cows with pedigree information had phenotypes. First, P-value was calculated based on the variance of the prediction error of the SNP effects on the first iteration. After that, 2 more iterations were performed to carry out the weighted single-step genome-wide association methodology, performed using genomic moving windows defined based on linkage disequilibrium. The significant SNPs and top 10 windows explaining the highest percentage of additive genetic variance were selected and used for QTL and gene annotation. The variants identified in our work overlapped with QTL from the animal QTL database on chromosomes 1 to 23, except for chromosome 4. The Gir breed is less studied than the Holstein breed and as such the animal QTL database is biased to Holstein results. Hence it is noteworthy that our GWAS had similarities with previously described QTL. These previously known QTL were related to milk yield, body height, rump angle, udder width, and udder depth. In total, 5 genes were annotated. Of these genes, FAM13A and CMSS1 had been previously related to bone and carcass weight in cattle.
Keywords: body conformation traits; Bos taurus indicus cattle; candidate genes; dairy cattle; genome-wide association